THAILAND AS A TOURISM DESTINATION: EXPLORING CHINESE OLDER ADULTS’ TRAVEL DECISION-MAKING THROUGH THE LENS OF THE S-O-R FRAMEWORK IN SOCIAL MEDIA CONTEXTS - YAN, LINA; DEEPRASERT, JIRAWAN; JIANG, SONGYU (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This study investigates the impact of factors affecting travel decision-making among older adults based on the S-O-R framework. Using case of Thailand as tourism destination, this study collects 602 Chinese older adults from Beijing, Shanghai, Guanghzou. Structural equation modeling (SEM) was applied to process the data. Findings reveal that information quality and KOL influence play a stronger role than system quality in shaping travel decisions. System quality does not directly influence travel decisions but exerts an indirect effect through perceived destination image and emotional experience. Additionally, emotional experience has a stronger impact than cognitive factors, indicating that older tourists are more influenced by emotional engagement than rational evaluation. KOL recommendations significantly enhance both perceived destination image and emotional connection, ultimately driving travel intention.